PENERAPAN MEDIA MIND MAPPING UNTUK MENINGKATKAN HASIL BELAJAR TEMATIK PADA TEMA ENERGI DAN PERUBAHAN ENERGI SISWA KELAS III SD NEGERI 2 ARDIREJO KECAMATAN KEPANJEN KABUPATEN MALANG - Winarsi (Jurnal Penelitian Ilmiah INTAJ, 2021)
Reflection and observation in class II SD Negeri 2 Ardirejo Kepanjen showed that learning is still teacher-centered, lack of student activity, and the use of media that is not according to student characteristics. This has an impact on the low student learning outcomes. To overcome these problems, learning is applied with the help of mind mapping media. The purpose of this research is to improve thematic learning outcomes on the theme of energy and its changes using mind mapping in third grade students of SDN 2 Ardirejo Kepanjen Malang. Classroom action research was carried out in two cycles. Each cycle is carried out in an allocated time of 3x35 minutes and goes through the stages of planning, implementing actions, observing, and reflecting. The research subjects consisted of teachers and third grade students of SD Negeri 2 Ardirejo Kepanjen. Data collection using test and non-test techniques. The data analysis technique used qualitative and quantitative data. The results showed that the teacher's skills in the first cycle got a score of 22.5 with good criteria then increased to 26 with very good criteria in the second cycle. Student activities in the first cycle got a score of 25 with very good criteria then increased to 28 with very good criteria in the second cycle. Student learning outcomes in the first cycle get 73.9% classical completeness and incomplete qualifications. Student learning outcomes in cycle II have increased with 91% classical completeness and complete qualifications. It can be concluded that learning with mind mapping media can improve thematic learning outcomes on the theme of energy and energy changes for third grade students of SD Negeri 2 Ardirejo Kepanjen.